Analysis of Context and Potentials of Restaurants in Koh Samui Toward Low Carbon Restaurant Based on BCG Concept - Phoochinda, Wisakha (Journal of Social Sciences and Humanities Research in Asia, 2025)
Climate change and the Bio-Circular-Green (BCG) economy model for sustainable development are critical issues, particularly in the restaurant sector, given its significant resource consumption and environmental impact. This study had three objectives: 1) to analyse the current situation and practices of restaurants in Koh Samui in transitioning towards a low-carbon society; 2) to examine internal and external factors and assess the sector's potential for adaptation to a low-carbon society under the BCG model, using SWOT analysis; and 3) to propose guidelines for strengthening this potential. A mixed-methods approach was employed, drawing on both secondary and primary data. Secondary data were collected through literature reviews on Koh Samui's low-carbon measures, while primary data were obtained from field surveys and in-depth interviews. The study involved 25 purposively selected restaurant operators, categorised into three groups: traditional medium-sized (n=6), contemporary medium-sized (n=3), and small fast-food restaurants (n=16). Data addressed aspects of business, energy, and environmental management, and were systematically analysed through documentary content analysis for secondary sources, descriptive statistics for quantitative survey data, and thematic analysis for qualitative interview data. These results were synthesised using SWOT analysis to assess potential and formulate guidelines. The findings indicate that the potential for a low-carbon transition under the BCG model centres on two main areas: BCG-aligned business activities (e.g., raw material sourcing, production, service) and energy and environmental management (e.g., energy, waste, water). Recommended guidelines include reducing carbon emissions alongside business operations (e.g., improving energy efficiency), maintaining the quality and experience of local cuisine, and promoting local identity and wisdom to create added value and support income distribution within the community.